Diagnostic Accuracy of Periapical Radiography in Detection and Measurement of the External Root Resorption in Primary Molars: A Single-Blind Prospective Clinical Study - Shirin Taravati; Zohreh Balak; Vahid Rakhshan (International Journal of Dentistry)
Introduction. Identifying the external root resorption plays an important role in treatment planning for deciduous teeth. Although proper accuracy of digital radiography in the diagnosis of external root resorption has been established in permanent dentition, it cannot be at all generalized to the primary root being superimposed by the succeeding permanent teeth. Interestingly, no study has assessed this in primary teeth yet. Thus, this study was undertaken for the first time. Methods. This was a single-blind prospective clinical diagnostic study performed on 501 observations (observed by 3 observers) pertaining to 167 roots of 45 maxillary/mandibular primary molars (in 6–8-year-old patients) which were indicated for extraction and did have succeeding permanent teeth. Digital parallel periapical radiographs were taken before dental extraction using a PSP sensor. Radiographs were printed and examined by two pediatric dentists. After the extraction, the extent of resorption was directly measured, twice, by third and fourth observers blinded to radiographic estimates. Radiographic errors and absolute errors (mm) were calculated. Various parameters were analyzed statistically. Results. Of the roots, 56.3% were really resorbed with (mean = 5.01 ± 2.10 mm). First/second observers failed to identify 19.6% and 38.3% of roots, respectively. Average errors were −0.77 ± 2.31 and 0.14 ± 2.19 mm in girls and boys, respectively (P=0.043, t-test). The factors “side, jaw, tooth type, and root type” did not affect errors (P>0.05). Average absolute errors were 1.79 ± 1.47  mm (significantly above zero, P<0.0005). No evaluated factor affected it (P>0.1). Actual lesion sizes correlated with errors (Pearson R = 0.682, P<0.0005) but not with absolute errors (P=0.464). Conclusion. Although many deciduous roots might be missed, digital radiography might still provide rather a good accuracy in diagnosis and measurement of external root resorption up to about 1.8 mm absolute error. Observers might overestimate resorption sizes in girls and in cases with actual lesions smaller than 3 mm. Size of the lesion can influence the direction of error (shortening/elongation), but not its directionless magnitude.